Biological Sinks for Carbon Dioxide – An Option for Agroforestry Systems in the Tropics - Goltenboth, Friedhelm; Milan, Paciencia P. (Annals of Tropical Research, 2015)
One of the core questions, that need to be answered in the present discussion about climate change, is how the increase of carbon dioxide content in the atmosphere can be minimized if not stopped. This Greenhouse Gas (GHG) is the main reason for the increase of average temperature. Under business as usual (BAU) conditions an increase in temperature between 1.7-4.5⁰C is expected during the next o 100 years. One option to counter this trend is through reforestation and the conservation of forests functioning as carbon sinks. Estimates are giving an amount of 60 Petagram (Pg) or 60 Gigatons (Gt) as exchange of carbon between the terrestrial ecosystems and the atmosphere annually. Tropical forests and agroforestry systems show promising options in the process of binding atmospheric carbon dioxide. The use of agroforestry methods, like the Rainforestation Farming strategy, open very interesting options due to ecological and economical advantages, while contributing to the reduction of carbon dioxide concentrations.